Heteropolygonatum hainanense (Asparagaceae), a new species endemic to Hainan (China) - Floden, Aaron J. (Phytotaxa, 2018)
Heteropolygonatum Tamura & Ogisu (1997: 950; Asparagaceae, Nolinoideae) differs from Polygonatum Miller (1754: without pagination) by two distinctive features: the perigone in Heteropolygonatum is imbricate whereas it is valvate in Polygonatum (Floden 2014b, Chen & Tamura 2000, Tamura et al. 1997a, b). The basic chromosome number in Heteropolygonatum is x =16 with distinctly bimodal karyotypes vs. the lower, although variable, basic chromosome number in Polygonatum is x = 9–15 (Tamura & Xu 2001, Yamashita & Tamura 2001, Chen & Tamura 2000, Tamura et al. 1997a, 1997b). Recently, several additional species have been added to this small genus, based on cytological data or morphological characters unique to Heteropolygonatum in tribe Polygonateae (Chao et al. 2013, Floden 2014b, Xiao et al. 2017). This genus now includes 12 species, with the addition of the one described here.